Exploring the Genetic Landscape of Octopus cyanea: Connectivity and Population Structure in Northern Waters of Sumatra - Ramadhaniaty, Mutia; Damora, Adrian; Moula, Intania; Fadli, Nur; Razi, Nanda Muhammad; Muchlisin, Zainal A (HAYATI Journal of Biosciences, 2026)
Octopus cyanea is an ecologically and economically important cephalopod with wide larval dispersal influenced by ocean currents. However, geographic isolation among island clusters in northern Sumatra may restrict gene flow and shape population structure. This study investigated the genetic diversity and connectivity of O. cyanea from five populations (Aceh Island, Weh Island, Banyak Island, Simeulue Island, and Nias Island) using mitochondrial cytochrome c oxidase subunit I (COI) sequences. A total of 21 individuals were successfully amplified, yielding 651 bp fragments. Sequence analysis revealed 11 haplotypes across populations, with haplotype diversity (Hd) ranging from 0.285 in Banyak Island to 0.800 in Aceh Island, and nucleotide diversity (π) between 0.001 and 0.009. Pairwise genetic distances varied from 0.000 to 0.004, with the highest divergence observed between Simeulue Island and Nias Island (0.004), while Aceh Island and Weh Island showed no differentiation. AMOVA indicated that most genetic variation occurred within populations (68.74%), with an overall Fst of 0.315, suggesting low to moderate genetic structuring. The haplotype network demonstrated shared haplotypes among four populations, whereas Simeulue Island harbored unique haplotypes, indicating partial genetic isolation. These results highlight substantial genetic connectivity among O. cyanea populations in northern Sumatra, facilitated by larval dispersal via ocean currents, but also emphasize localized divergence in Simeulue Island. The findings provide critical baseline data for developing ecosystem-based fisheries management, supporting shared stock strategies while accounting for population-specific conservation needs.